Prime Minister’s Directions on proactive implementation of measures to cope with the risk of droughts, waters shortages, and salinity intrusion in the dry season 2020-2021 in the Mekong River Delta-Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Decree directs localities to implement drought adaptation measures crisis using the recommendations from the Ministry of Agriculture and Rural Development (including the risk maps/CS-MAP on salinity intrusion).